Glaucoma and Risk of Fractures: A Systematic Review, Meta-Analysis, and Network Meta-Analysis - Gallo Afflitto, Gabriele; Aiello, Francesco; Swaminathan, Swarup S; Matarazzo, Francesco; Stuart, Kelsey V; Khawaja, Anthony P; Costagliola, Ciro; Nucci, Carlo (Journal of glaucoma, 2025)
Glaucoma is associated with a significant risk of bone fracture. Comprehensive patient education and targeted interventions are crucial to mitigating this risk and improving outcomes. To evaluate the risk ratio (RR) and hazard ratio (HR) of fractures in subjects with glaucoma compared with healthy controls. The study protocol (CRD42024527785) was registered prospectively. PubMed, EMBASE, and Web of Science were searched from their inception to April 2024. Glaucoma was identified by the presence of a visual field defect (GVFD) consistent with glaucomatous optic neuropathy, ICD codes (or similar disease-classifying codes), and self-report. Visual field damage severity was classified using the Hodapp-Anderson-Parrish criteria, with study-specific criteria for severity deemed suitable on a case-by-case basis. Both frequentist inference meta-analysis and Bayesian network meta-analysis (NMA) were conducted. Seven articles were deemed eligible for synthesis, covering a combined population of 570,694 subjects and reporting a total of 45,957 fractures. Bayesian NMA indicated that both mild and severe glaucomatous visual field defects were associated with an 80% increased RR of fractures compared with healthy counterparts [RR mild: 1.8, 95% Credible Interval (95%CrI): 1.5 to 2.3; RR severe: 1.8, 95% CrI: 1.3-2.4]. A higher HR of fractures was observed in individuals with mild (HR: 1.2; 95% CrI: 1.1-1.3) and moderate (HR: 1.4; 95% CrI: 1.1-1.8) glaucoma compared with healthy subjects. Low- to moderate-quality evidence indicates a significant association between glaucoma and increased fracture risk, with individuals with mild to moderate GVFD showing the highest HR and RR of fractures. These results emphasize the role of patient education and the necessity for targeted interventions and preventive strategies to mitigate the risk of fracture among affected individuals.